A Neutrosophic Approach to Solving First-Order Differential Equations: Applications to Heat Convection with Uncertain Initial Conditions - Said Broumi; M. Shanmugapriya; R. Sundareswaran (Neutrosophic Sets and Systems)
A solution procedure for the system of first-order ODEs is developed and demonstrated with numerical examples.